MIND MAPPING SEBAGAI KUNCI PENINGKATAN PEMAHAMAN KONSEP PERKEMBANGAN TEKNOLOGI PADA SISWA KELAS 4 SDN 01 BABAKAN - Astriansyah, Lusi Nur; Rasiman; Purnamasari, Iin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This quasi-experimental pretest–posttest control group study investigated the effect of the Mind Mapping method on learning outcomes for the concept of technological development among fourth-grade students at SDN 01 Babakan. Forty-three students participated: 22 in the experimental group (audio-visual Mind Mapping) and 21 in the control group (image-based elaboration). Valid and reliable instruments were used, and data were analyzed via normality (Kolmogorov–Smirnov) and homogeneity (Levene’s) tests, followed by paired-samples and independent-samples t-tests at α = 0.05. Results showed the experimental group’s mean score increased from 55.00 to 80.00 (gain = 25.00; 45.5 %), while the control group’s mean score rose from 54.50 to 65.00 (gain = 10.50; 19.3 %). Significant improvements were confirmed by the paired-samples t-test (t(21) = 15.32, p < .001, Cohen’s d = 3.26) and the independent-samples t-test (t(41) = 6.45, p < .001, Cohen’s d = 2.03). These findings endorse the integration of Mind Mapping into elementary science instruction. Future research should explore digital Mind Mapping tools, conduct longitudinal studies on retention, and examine moderating factors such as learning styles and technological proficiency.